A Co3O4–CeO2 functionalized SBA-15 monolith with a three-dimensional framework improves NOx-assisted soot combustion1. Issue 34 (15th April 2015) - Yang, Qiongqiong; Gu, Fangna; Tang, Yufang; Zhang, Hui; Liu, Qing; Zhong, Ziyi; Su, Fabing
<x xml:space="preserve">Abstract</x> Co3O4–CeO2/SBA-15 monolith can efficiently filter and catalyze the soot particles. The optimized one exhibited a low T10 (293 °C) and T90 (378 °C).